+0  
 
+1
142
2
avatar+184 

If $f(x)=\dfrac{a}{x+2}$, solve for the value of $a$ so that $f(0)=f^{-1}(3a)$.

 Apr 30, 2021
 #1
avatar+795 
+1

0 = (a-6a)/3a

-5a = 0

a = 0. 

laugh

 Apr 30, 2021
 #2
avatar+121048 
+1

f(0)  =   a/2

 

Find  the  inverse

 

y =   a / ( x + 2)           get  x  by itself

 

(x + 2) y  =  a

 

x + 2  =  a / y

 

x =   a / y   -  2                 "swap"  x  and  y

 

y =  a/x   -  2         =   the  inverse  = f-1

 

f-1 (3a)   =    a / ( 3a)  -  2    =   (1/3)  - 2   =  -5/3

 

So

 

f (0)  =  f-1 (3a)

 

a/2  = -5/3

 

a  = 2 (-5/3)   =   -10/3

 

 

cool cool cool

 Apr 30, 2021

63 Online Users

avatar
avatar